Electro‐optic polymer/titanium dioxide hybrid core ring resonator modulators. Issue 6 (6th September 2013) - Qiu, Feng; Spring, Andrew M.; Yu, Feng; Aoki, Isao; Otomo, Akira; Yokoyama, Shiyoshi
<x xml:space="preserve">Abstract</x> Compact electro‐optic (EO) modulators are desirable for a number of applications. In this study, a ring modulator has been fabricated in the titanium dioxide (TiO2) core and EO polymer cladding waveguide structure. A 250‐nm thick TiO2 core was utilized to minimize the ring radius down to 100 μm, to avoid using the top cladding between the EO polymer and the electrode, and to improve the poling efficiency. The resonance obtained by the ring modulator was observed to shift by 0.02 nm/V due to the enhanced in‐device EO coefficient of 105 pm/V. A modulation depth of 3 dB was observed at the frequency response function at 20 kHz using 2‐V Vp–p clock signal. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>